Mental health challenges faced by professional athletes - Szczepanek, Dawid; Szczurek, Katarzyna; Biecka, Adrianna; Wyrzykowski, Mikołaj (Quality in Sport, 2025)
Background: Sport psychiatry is a dynamic and constantly developing discipline of medicine. Professional athletes may experience a variety of mental health problems that influence their everyday life and sport performance. Therefore, the potential risk factors for developing mental disease should be known to coaches and physicians to provide adequate help for athletes. Materials and methods: We reviewed publications obtained from PubMed and Google Scholar. Articles were selected on the basis of keywords such as “sport psychiatry”, “mental health in athletes”, and “depression in professional sport”. For the final analysis, the eligible articles were published from 2015--2024. Results: The prevalence of mental disorders varied across the analyzed studies. The presence of symptoms depends on the type of sport performed by the individual, past history of psychiatric diseases or sex. Additionally, studies have used different types of evaluation tools, which may influence the results. Conclusions: Mental health diseases are present in this group, in some cases more frequently than in the general population. Professional athletes should be watched carefully for the potential development of psychiatric symptoms, especially in the most vulnerable groups. There is also a need for further studies with validated athlete research tools for more reliable results.